Position of the mandibular incisors, gingival recession and airway dimensions after treatment with Jasper Jumper: 10-year follow-up - Moura, Wilana da Silva (2020)
Introduction: The aim of this study was to evaluate long-term results regarding position and gingival recession of the mandibular incisors, and airway dimensions after treatment with the Jasper Jumper appliance. Material and Methods: The patients were divided in 2 groups: Jasper group was constituted of 16 patients treated with Jasper Jumper appliance for a mean period of 2.06 years (SD, 0.21) and evaluated in the follow-up period of 11.88 years (SD, 0.49). The mean initial age was of 12,49 years (SD, 1.61), the mean final age of 14.55 years (SD, 1.17), and the mean age at the follow-up of 26.43 years (SD, 1.24); Control group was constituted of 16 age-matched untreated Class II patients. Results from the treated group were compared to crosssectional measurements obtained from lateral cephalograms of untreated Class II individuals matched to the age, skeletal age and sex distribution with the treated patients in each time of evaluation (T1, T2, and T3). The presence of gingival recession, the extent of gingival recession, and the position of the mandibular incisors were evaluated in intraoral photographs, digital models, and lateral cephalograms at 3 stages in the Jasper group. Skeletal and airway dimensions were evaluated using Dolphin Imaging software in both groups. Statistical analyses were performed by Dependent t, Wilcoxon, Pearsons Correlation, Repeated measures ANOVA, Independent t and Mann-Whitney tests, at P< 0.05. Results: The presence of gingival recession increased over time and was observed in 6 (9.4%), 12 (18.8%), and 24 (37.5%) of the teeth at pretreatment, posttreatment, and follow-up, respectively. There was a significant increase in labial inclination and protrusion of the mandibular incisors after treatment and a significant increase in the extent of the gingival recession in the follow-up period and in the long-term total time. There was no correlation between the extent of gingival recession and the labial inclination and protrusion of the mandibular incisors. Minimal sagittal skeletal changes were observed in both groups. Vertical skeletal dimensions and clockwise rotation of the occlusal plane were significantly greater in the Jasper group than in the Control group at T2 and T3. The lower airway was significantly greater in the Jasper group than in the Control group at T2. The upper and lower airway were similar in both groups at T3. Conclusion: Correlation between the extent of gingival recession, and the labial inclination and protrusion of the mandibular incisors was not observed. The lower airway was significantly greater in the Jasper group than in the Control group at T2, but at T3 significant difference between the groups was not observed.